Ikigai as Student High Order Literacy Skills Intrinsic Motivation Learning Template - Hikmawan, Rizki; Suherman, Ayi; Fauzi, Ahmad; Mubarak, Ibnu (LPPM Undiksha, 2020)
This study aims to develop instructional design that include Ikigai concept to improve students High Order Literacy Skills competence in accordance to standard needed in industrial 4.0 era. Product development is done by Research and Development (R&D) Method with Akker procedure scheme. On the field of Informatic Education, our main concern is student that can be described as skilled programmer often have poor communication or collaboration skills with societies and vice-versa, student with good social skills often has poor technical skill. However, when the students have clear life-goal, those lack of social or technical skills are gradually improved. In this study, we cultivate student's intrinsic motivation by utilize Ikigai concept on teaching and learning activities. The result show that when the students have clear life-goal, those lack of social or technical skills are gradually improved. Furthermore, by properly using Ikigai as motivation template, it could be the most important factor that help eastern culture people achieve self-actualization.